Credit Monitoring, Recovery Strategies and Performance of Commercial Banks in Uganda: A Case Study of Centenary Bank Kabale Branch - Protase, Mubangizi (Kabale University, 2022)
A Dissertation Submitted to the Directorate of Postgraduate Training in Partial Fulfilment of the Requirements for the Award of a Master’s Degree in Project Planning and Management of Kabale University